BREASTFEEDING: THE DIFFICULTIES IN ORGANIZING AND THEIR OVERCOMING - M. V. Gmoshinskaya (Union of pediatricians of Russia, 2012)
The issue presents three main groups of factors that contribute to the support of a full lactation; some difficulties of breastfeeding, which are often the cause of its early termination are considered. Difficulties in the organization of breastfeeding are presented in the form of five groups: 1 - psychological and social; 2 - organizational; 3 - from health workers; 4 - from the mother; 5 - from the child. It is shown that the breastfeeding dominant (a part of the motherhood dominant) has a leading role in the establishment of lactation and its duration. Conscious attitude to the need for breastfeeding for at least the first year of life is formed only in those mothers who throughout their adulthood (girl - adolescent - woman) formed a mother dominant. There is demonstrated how to make a supplementary feeding with expressed breast milk using special devices.